PENGARUH STRATEGI THINK TALK WRITE (TTW) TERHADAP KETERAMPILAN MENULIS PUISI SISWA KELAS II SDN 79 PEKANBARU - Vopy Dwi Zasria; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to description poetry writing skills difference between the experimental class and control class. This research is a quasi-experimental research with design research